COVID-19 AND TOURISM: A DESCRIPTIVE STUDY OF THE STRATEGIES OF YOUTH MARINE TOURISM BUSINESS ACTORS ON DERAWAN ISLAND DURING THE COVID-19 PANDEMIC: COVID-19 DAN PARIWISATA: STUDI DEKSRIPTIF STRATEGI PEMUDA PELAKU USAHA WISATA BAHARI PULAU DERAWAN KETIKA PANDEMI COVID-19 - Ahmad Hidayah; Hanafi Saputra; Kamilah Dwi Kurniawati; Agung Prajulianto; Ziya Ibrizah; Yuhelna (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This paper aims to analyze the strategies of young entrepreneurs in the marine tourism industry on Derawan Island in facing the challenges of the COVID-19 pandemic. The study employs a qualitative approach using purposive and snowball sampling techniques for informant selection. Data collection was carried out through interviews and field observations. The research applies James C. Scott’s survival strategy theory to analyze the phenomena under investigation. The results of the study indicate that young entrepreneurs in the marine tourism sector on Derawan Island were a vulnerable group during the COVID-19 pandemic. To address these challenges, the young entrepreneurs engaged in several survival strategies, including returning to fishing and adjusting the pricing of tourism packages during the new normal period.